2006
DOI: 10.1097/01.brs.0000245851.55012.f1
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Spinal Canal Expansion Following Cervical Laminoplasty: A Computer-Simulated Comparison Between Single and Double-Door Techniques

Abstract: Our investigation provides insight into canal expansion after laminoplasty. The increased amount of canal following laminoplasty can be predicted by the regression equations. This may allow preoperative determination of the optimal size of the opening needed to establish adequate canal space for the spinal cord. Both single and double-door techniques of laminoplasty provide sufficient room for posterior migration of the spinal cord, although gaining different canal expansion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 27 publications
1
32
0
1
Order By: Relevance
“…In such cases, traction, tethering, and/or kinking of the nerve root secondary to posterior shift of the spinal cord may result, which has been viewed as a main factor in postoperative C5 nerve root palsy [13][14][15][16][17][18]. Wang et al [19] pointed out that excessive opening creates a wider epidural space, leading to excessive formation of epidural scar tissue. Although the laminoplasty opening size (LOS) largely determines the amount of canal expansion created during laminoplasty, but the relationship between the LOS and the amount of canal expansion has remained unclear.…”
Section: Introductionmentioning
confidence: 99%
“…In such cases, traction, tethering, and/or kinking of the nerve root secondary to posterior shift of the spinal cord may result, which has been viewed as a main factor in postoperative C5 nerve root palsy [13][14][15][16][17][18]. Wang et al [19] pointed out that excessive opening creates a wider epidural space, leading to excessive formation of epidural scar tissue. Although the laminoplasty opening size (LOS) largely determines the amount of canal expansion created during laminoplasty, but the relationship between the LOS and the amount of canal expansion has remained unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Other authors have also expressed the idea that excessive opening of the lamina may lead to post-operative C5 nerve root palsy [16,17]. Wang et al [18] pointed out that excessive opening also creates a wider epidural space and leads to the formation of more epidural scar tissues than normally expected.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a few studies have reported laminoplasty using computer-assisted analysis. Wang and colleagues [5] studied canal expansion with both single open-door laminoplasty and double open-door laminoplasty using a computer-assisted technique. They concluded that the increased amount of canal following laminoplasty could be predicted by regression equations.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from the width of the bone gutter (d), the angle of the lifted lamina () is of crucial importance for clinical outcomes of EL since it is closely linked with canal enlargement [5]. Clinically, studies have shown that neurologic improvement directly correlates with the degree of canal expansion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation